The Sage international encyclopedia of mass media and society - Merskin, Debra L. (A SAGE reference publication, 2020)
"The SAGE International Encyclopedia of Mass Media and Society discusses media around the world in their varied forms-newspapers, magazines, radio, television, film, books, music, websites, social media, mobile media-and describes the role of each in both mirroring and shaping society. This encyclopedia provides a thorough overview of media within social and cultural contexts, exploring the development of the mediated communication industry, mediated communication regulations, and societal interactions and effects"--